Edukasi Enam Langkah Mencuci Tangan Sebagai Upaya Untuk Menerapkan Perilaku Hidup Bersih Dan Sehat (PHBS) - Syalwa Anggun Indiani; Aulia Putri Rahmawati; Dhita Sukma Anggraeni; Fitriyanti; Rosandra Firdi Silviana; Yuwanti (Jurnal Pengabdian kepada Masyarakat Cahaya Negeriku, 2022)
Background: The behavior of washing hands with soap is one form of effort to prevent the spread of COVID-19 that can be applied early on to children. Clean and Healthy Living Behavior is an effort to provide information and education to increase knowledge in the school, household and surrounding environment. Aims: provide knowledge and understanding to children about PHBS. Results: There are 20 children who can practice the steps of washing their hands properly and 8 other children are quite familiar with the education and counseling delivered by the community service team. Conclusion: This educational or counseling activity can increase concern for the importance of clean and healthy living by washing hands, especially in children and communities in the face of the spread of the COVID-19 pandemic in everyday life.